The correct name for Asparagus fasciculatus Thunb. (Asparagaceae) - Manning, John (African Biodiversity & Conservation, 2026)
The name Asparagus fasciculatus Thunb. (1818) for a South African species in the genus is an illegitimate later homonym of the northern Australian A. fasciculatus R.Br. (1810). The later taxonomic synonym A. consanguineus (Kunth) Baker is available for the South African taxon and is thus the correct name for it.